MiR-34a and stroke: Assessment of non-modifiable biological risk factors in cerebral ischemia. (July 2019) - Ren, Xuefang; Engler-Chiurazzi, Elizabeth B.; Russell, Ashley E.; Sarkar, Saumyendra N.; Rellick, Stephanie L.; Lewis, Sara; Corbin, Deborah; Clapper, Jared; Simpkins, James W.
Abstract: Aging of the nervous system, and the occurrence of age-related brain diseases such as stroke, are associated with changes to a variety of cellular processes controlled by many distinct genes. MicroRNAs (miRNAs), short non-coding functional RNAs that can induce translational repression or site-specific cleavage of numerous target mRNAs, have recently emerged as important regulators of cellular senescence, aging, and the response to neurological insult. Here, we focused on the assessment of the role of miR-34a in stroke. We noted increases in miR-34a expression in the blood of stroke patients as well as in blood and brain of mice subjected to experimental stroke. Our methodical genetic manipulation of miR-34a expression substantially impacted stroke-associated preclinical outcomes and we have in vitro evidence that these changes may be driven at least in part by disruptions to blood brain barrier integrity and mitochondrial oxidative phosphorylation in endothelial cells. Finally, aging, independent of brain injury, appears to be associated with shifts in circulating miRNA profiles. Taken together, these data support a role for miRNAs, and specifically miR-34a, in brain aging and the physiological response to age-related neurological insult, and lay the groundwork for future investigation of this novel therapeutic target. Highlights: microRNAs, namely miR-34a, may regulate brain aging and age-related diseases. In both mice and humans, miR-34a played an important role in stroke pathology. Manipulation of miR-34a impacts blood brain barrier and mitochondrial function. microRNAs may represent novel therapeutic targets for aging and stroke.